Brand effectiveness audit : a case study of Thai Tuan Textile and Garment Co., Ltd., Vietnam - Nguyen Ngoc Ha; Truong, Quang; Broustai, Joel Francois; Sununta Siengthai; The French Government; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2004)
With eleven years presence in the market, Thai Tuan TG has strongly convinced consumers by its high and stable quality of its products, an advantage hardly owned by most private textile companies in Vietnam. As a result, its brand "Thai Tuan" has been recognized by a growing number of consumers, despite its late introduction of six years ago. However, to ensure its sustainability in the future, building wide brand name recognition is less than sufficient. It is more essential that Thai Tuan TG makes its brand be liked and loved by customers. This requires the company to set up a clear identity as well as a favorable personality for its brand. In this sense, the research aims at investigating the brand of Thai Tuan TG by way of conducting a comprehensive brand audit. This involves both brand inventory and exploratory analysis for Thai Tuan TG and its competitors. The results of the analysis brings out that Thai Tuan has a relatively strong brand inventory, which remains few facets to be strengthened. However, both Thai Tuan's brand identity and personality need to be further improved. Especially, Thai Tuan must ensure a match between its brand identity and brand personality, a critical requirement for future success.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M. BA.) - Asian Institute of Technology, 2004
Keywords: Textile industry -- Vietnam; Product management -- Vietnam